2012
DOI: 10.1109/tpel.2012.2183894
|View full text |Cite
|
Sign up to set email alerts
|

Design and Tuning of a Modified Power-Based PLL for Single-Phase Grid-Connected Power Conditioning Systems

Abstract: One of the most important aspects for the proper operation of the single-phase grid-tied power-conditioning systems is the synchronization with the utility grid. Among various synchronization techniques, phase locked loop (PLL) based algorithms have found a lot of interest for the advantages they present. Typically, the single-phase PLLs use a sinusoidal multiplier as the phase detector (PD). These PLLs are generally referred to as the power-based PLL (pPLL). In this paper, the drawbacks associated with the pP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(118 citation statements)
references
References 38 publications
0
117
0
1
Order By: Relevance
“…This can be done by making the α component equal to the phase voltage and the β component equal to zero [9]. However, this produces a mirror-frequency term in the obtained voltage vector, which needs to be removed, a filter or a decoupling network can be used for this purpose.…”
Section: A Quadrature Signal Generator (Qsg)mentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by making the α component equal to the phase voltage and the β component equal to zero [9]. However, this produces a mirror-frequency term in the obtained voltage vector, which needs to be removed, a filter or a decoupling network can be used for this purpose.…”
Section: A Quadrature Signal Generator (Qsg)mentioning
confidence: 99%
“…Assuming perfect tracking of the fundamental component, i.e. , the error signal (8) can be expressed as (9). It is observed that the phase error consists of two harmonic components of orders n±1.…”
Section: B Three-phase Atomentioning
confidence: 99%
“…A major challenge of PLLs is how to quickly and accurately estimate the phase angle and frequency when the grid voltage is distorted. To overcome this challenge, combining filtering techniques into the structure of PLLs has been proposed in the literature [13][14][15][16][17][18][19][20][21][22][23][24]. Reference [14] used a double, or more synchronous reference frame (DSRF/MSRF), to realize the decoupling between the fundamental negative sequence and the positive sequence components, and then locking the phase angle by extracting the fundamental positive sequence component, which can realize a fast and dynamic response.…”
Section: Introductionmentioning
confidence: 99%
“…Various synchronization techniques have been proposed in literatures. The zero crossing detection methods [3], the space-vector filtering (SVF) method [4], the artificial neural networks (ANN) method [5], the recursive weighted least-squares estimation (WLSE) algorithm [6], the discrete Fourier transform (DFT) and its modifications [7], the methods based on the concept of adaptive notch filtering (ANF) [8], the Kalman filtering technique [9], the frequency-locked loop (FLL) methods [10], three phase open-loop phase-locked method [11] and the phase-locked loop (PLL) algorithms [12,13] are among the existing synchronization techniques.…”
Section: Introductionmentioning
confidence: 99%